Affordances and constraints of project-based learning in asynchronous online distance education: A mixed-methods empirical study in a biotechnology course - Kismiati, Dyah Aniza; Yani, Ahmad (Jurnal Sinar Edukasi, 2026)
Background/Problem: The implementation of Project-Based Learning (PjBL) in fully asynchronous Online Distance Learning (ODL) contexts presents a distinctive dual structure of affordances and constraints that remains underexplored, particularly in science disciplines requiring hands-on competence. This study addresses this gap by systematically mapping the affordance-constraint landscape of PjBL in a Biotechnology course at Universitas Terbuka (UT), Indonesia’s national open university. Research Questions: (1) What types and frequencies of difficulties do students experience during PjBL project execution in an asynchronous ODL tutorial? (2) How do students perceive PjBL across ten dimensions of learning experience? Methodology: A concurrent mixed-methods design was employed, integrating descriptive survey and qualitative content analysis. A total of 144 Biology Education students distributed across 17 online tutorial classes participated through total sampling during the 2025 academic year. Data were collected using a researcher-developed and expert-validated 28-item Google Form questionnaire. Findings: Project timeline constraints were the dominant constraint (n = 66), followed by LKM instruction clarity (n = 15), project title–materials mismatch (n = 14), and tutor facilitation (n = 13). The 10-item Likert scale (α = 0.980) revealed positive endorsement rates of 88.9%–94.4%, with means of 2.88–3.14. Implications: PjBL in ODL operates within a high-affordance, single-dominant-constraint profile. Three evidence-based recommendations are proposed: initiating the PjBL cycle at Session 5 or 6, establishing a pre-project synchronous session, and redesigning project topics around locally accessible materials.